Research progress of risk factors and early diagnostic biomarkers of gout-induced renal injury - Wang, Sheng; Zhang, Liyun; Hao, Dongsheng; Wang, Lei; Liu, Jiaxi; Niu, Qing; Mi, Liangyu; Peng, Xinyue; Gao, Jinfang (Frontiers in Immunology, 2022)
Gout renal injury has an insidious onset, no obvious symptoms, and laboratory abnormalities in the early stages of the disease. The injury is not easily detected, and in many cases, the patients have entered the renal failure stage at the time of diagnosis. Therefore, the detection of gout renal injury–related risk factors and early diagnostic biomarkers of gout renal injury is essential for the prevention and early diagnosis of the disease. This article reviews the research progress in risk factors and early diagnostic biomarkers of gout renal injury.